2008
DOI: 10.1118/1.2995760
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the dosimetric results of three uniformity regularization methods in terms of expected treatment outcome

Abstract: In IMRT treatment plan optimization there are various methods that try to regularize the variation of dose nonuniformity using purely dosimetric measures. However, although these methods can help in finding a good dose distribution, they do not provide any information regarding the expected treatment outcome. When a treatment plan optimization is performed using biological measures, the final goal should be some indication about the expected tumor control or normal tissue complications, which is the primary go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…All the inverse optimized treatment plans were based on HIPO using the modulation restriction methods, which are investigated in conjunction with radiobiological dose non-uniformity evaluation measures in order to estimate their expected clinical impact [13]. A certain pattern of dose non-uniformities produces a certain radiobiological response.…”
Section: Purposementioning
confidence: 99%
“…All the inverse optimized treatment plans were based on HIPO using the modulation restriction methods, which are investigated in conjunction with radiobiological dose non-uniformity evaluation measures in order to estimate their expected clinical impact [13]. A certain pattern of dose non-uniformities produces a certain radiobiological response.…”
Section: Purposementioning
confidence: 99%
“…Furthermore, in order to more closely predict the clinical outcome of a treatment, the tumor control probability (TCP), normal tissue complication probability (NTCP), and uncomplicated tumor control probability (P + ), which depend on radiobiological parameters, have also been used for plan evaluation both in external beam radiotherapy (EBRT) and brachytherapy. [21][22][23][24] In various cases they have also been used as an alternative or in conjunction with dose-volume-based criteria during the treatment plan optimization procedure [25][26][27] and the significance of doseresponse-based objective functions has been suggested for intensity modulated (external) radiation therapy (IMRT) in several papers. [28][29][30][31] In most of the cases it was shown that for the same or better target coverage dose-response-based optimization resulted in improved sparing of critical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The time-domain waveform of half sine pulse signal.According to the kinetic law, the dynamic equation of the hydrophone m is as follows[4] mx cx kx ky cy +…”
mentioning
confidence: 99%